Enhancement and desert - Douglas, Thomas (Polit Philos Econ, 2018)
It is sometimes claimed that those who succeed with the aid of enhancement technologies deserve the rewards associated with their success less, other things being equal, than those who succeed without the aid of such technologies. This claim captures some widely held intuitions, has been implicitly endorsed by participants in social–psychological research and helps to undergird some otherwise puzzling philosophical objections to the use of enhancement technologies. I consider whether it can be provided with a rational basis. I examine three arguments that might be offered in its favour and argue that each either shows only that enhancements undermine desert in special circumstances or succeeds only under assumptions that deprive the appeal to desert of much of its dialectic interest.